Landscapes, literary geography and national identity - Vilariño Picos, Teresa (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In the words of Mario Valdés and Linda Hutcheon, the study of literature needs to be contained within the limits of that which these two authors call the History of Comparative Literary Culture or Comparative Historiography of Literary Culture. Here, the literary phenomenon transcends aesthetic and formal levels, taking into consideration how other fields such as the political, anthropological, economic, geographic, historical, demographic, and sociological articulate the contexts of a literary community. The research lines that I wish to explore throughout this paper seek to explain, within a general theory of the essay, the way the national cultural imaginary has developed in Spain and Portugal, as a system amid sucessive shared end of the century value systems, extending into the the first decades of the 20th century. We are dealing with a “collective imaginary”, a “continuity”, in azorinian terms, stemming from an interpretation of the verbal landscape –the physical expression of human works, geographical, and above all, cultural landscape.